BpeB, a major resistance‐nodulation‐cell division transporter from Burkholderia cenocepacia: construct design, crystallization and preliminary structural analysis. Issue 11 (2nd November 2018) - Horikawa, Tomonari; Hung, Li-Wei; Kim, Heung-Bok; Shaya, David; Kim, Chang-Yub; Terwilliger, Thomas C.; Yamashita, Eiki; Aoki, Maho; Okada, Ui; Murakami, Satoshi
Abstract : BpeB, which is a major multidrug‐efflux transporter in Burkholderia cenocepacia, has a C‐terminal region that extends beyond those of other homologous resistance‐nodulation‐cell division transporters such as AcrB and MexB. Comparative modeling helped to identify truncation variants that could aid the crystallization of BpeB without eliminating its molecular functions. Abstract : Burkholderia cenocepacia is an opportunistic pathogen that infects cystic fibrosis patients, causing pneumonia and septicemia. B. cenocepacia has intrinsic antibiotic resistance against monobactams, aminoglycosides, chloramphenicol and fluoroquinolones that is contributed by a homologue of BpeB, which is a member of the resistance‐nodulation‐cell division (RND)‐type multidrug‐efflux transporters. Here, the cloning, overexpression, purification, construct design for crystallization and preliminary X‐ray diffraction analysis of this BpeB homologue from B. cenocepacia are reported. Two truncation variants were designed to remove possible disordered regions based on comparative sequence and structural analysis to salvage the wild‐type protein, which failed to crystallize. The 17‐residue carboxyl‐terminal truncation yielded crystals that diffracted to 3.6 Å resolution. The efflux function measured using minimal inhibitory concentration assays indicated that the truncation decreased, but did not eliminate, the efflux activity of the transporter.